LEGAL PROTECTION FOR CONSUMERS OF ONLINE TRANSPORTATION SERVICE GOJEK - Astrid Aulia Rachman; Gianto Al Imron (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
This research aims to study the legal protection for consumers of online transportation service users if something happens that is detrimental to the consumer for errors or omissions from the driver or from the business provider of application service providers. The author uses the normative juridical method The results of the study show that there are no regulations governing legal protection for consumers of online transportation service users if the consumers are harmed due to errors, negligence on the part of the driver, or from the business provider of application service providers. The purpose of this study is to determine the legal relationship between GOJEK consumers and GOJEK transportation service business operators to determine the liability of their parties, as well as knowing what legal remedies can be done by consumers in the event of a loss by consumers in using GOJEK transportation services. The government should act as a regulator in facilitating the public with the regulations on online transportation services as a means to protect the rights of consumers